First transcriptome analysis of the venom glands of the scorpion Hottentotta zagrosensis (Scorpions: Buthidae) with focus on venom lipolysis activating peptides - Salabi, Fatemeh; Jafari, Hedieh; Mahdavinia, Masoud; Azadnasab, Reza; Shariati, Saeedeh; Baghal, Mahsa Lari; Tebianian, Majid; Baradaran, Masoumeh (Frontiers in Pharmacology, 2024)
Introduction Scorpion venom is a rich source of biological active peptides and proteins. Transcriptome analysis of the venom gland provides detailed insights about peptide and protein venom components. Following the transcriptome analysis of different species in our previous studies, our research team has focused on the Hottentotta zagrosensis as one of the endemic scorpions of Iran to obtain information about its venom proteins, in order to develop biological research focusing on medicinal applications of scorpion venom components and antivenom production. To gain insights into the protein composition of this scorpion venom, we performed transcriptomic analysis. Methods Transcriptomic analysis of the venom gland of H. zagrosensis, prepared from the Khuzestan province, was performed through Illumina paired-end sequencing (RNA-Seq), Trinity de novo assembly, CD-Hit-EST clustering, and annotation of identified primary structures using bioinformatics approaches. Results Transcriptome analysis showed the presence of 96.4% of complete arthropod BUSCOs, indicating a high-quality assembly. From total of 45,795,108 paired-end 150 bp trimmed reads, the clustering step resulted in the generation of 101,180 de novo assembled transcripts with N50 size of 1,149 bp. 96,071 Unigenes and 131,235 transcripts had a significant similarity (E-value 1e-3) with known proteins from UniProt, Swissprot, Animal toxin annotation project, and the Pfam database. The results were validated using InterProScan. These mainly correspond to ion channel inhibitors, metalloproteinases, neurotoxins, protease inhibitors, protease activators, Cysteine-rich secretory proteins, phospholipase A enzymes, antimicrobial peptides, growth factors, lipolysis-activating peptides, hyaluronidase, and, phospholipase D. Our venom gland transcriptomic approach identified several biologically active peptides including five LVP1-alpha and LVP1-beta isoforms, which we named HzLVP1_alpha1, HzLVP1_alpha2, HzLVP1_alpha3, HzLVP1_beta1, and HzLVP1_beta and have extremely characterized here. Discussion Except for HzLVP1_beta1, all other identified LVP1s are predicted to be stable proteins (instability index <40). Moreover, all isoform of LVP1s alpha and beta subunits are thermostable, with the most stability for HzLVP1_alpha2 (aliphatic index = 71.38). HzLVP1_alpha2 has also the highest half-life. Three-dimensional structure of all identified proteins compacts with three disulfide bridges. The extra cysteine residue may allow the proteins to form a hetero- or homodimer. LVP1 subunits of H. zagrosensis potentially interact with adipose triglyceride lipase (ATGL) and hormone-sensitive lipase (HSL), two key enzymes in regulation of lipolysis in adipocytes, suggesting pharmacological properties of these identified proteins.